Collaborative Sustainable Development Strategy: Linking Dynamic Capabilities To Sustainable Business Performance In The Indonesian Cocoa Value Chain - Asni Mustika Rani; Agus Rahayu; Lili Adi Wibowo; Alfira Sofia; Umari Abdurrahim Abi Anwar (Yayasan Vifada Cendikia Indonesia, 2025)
Sustainability pressures in agricultural value chains are no longer distant policy discussions. They now influence how firms organize sourcing, production, and distribution on a daily basis. In Indonesia’s cocoa sector, these pressures go beyond compliance. Firms are increasingly required to embed environmental and social considerations into their operational decisions if they wish to maintain market access and competitiveness. This study examines how Dynamic Sustainable Supply Chain Capabilities (DSSCC) relate to Sustainable Business Performance (SBP) and whether a Collaborative Sustainable Development Strategy (CSDS) serves as the mechanism linking the two. Survey data were collected from 40 downstream bean-to-bar cocoa firms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal a clear pattern. DSSCC strongly supports the formation of CSDS, indicating that leadership commitment, sustainable sourcing, responsible processes, sustainable delivery systems, technology management, and social capability create the internal conditions necessary for collaboration. However, DSSCC does not directly improve SBP. Performance gains emerge when these capabilities are enacted through structured collaboration. CSDS fully mediates the relationship between DSSCC and SBP, suggesting that sustainability outcomes improve when firms work closely with farmers, buyers, communities, and regulators rather than relying solely on internal initiatives. The study draws on the Resource-Based View, Dynamic Capabilities Theory, Stakeholder Theory, and Institutional Theory to frame sustainability transitions as relational processes that unfold across value chains. The findings underline a practical implication: strengthening internal capability is important, but sustainable performance depends on how effectively firms translate that capability into collective action.